PENGEMBANGAN DESAIN BLENDED LEARNING UNTUK PROGRAM PELATIHAN PENDALAMAN MATERI IPA BERBASIS KEBUTUHAN MAHASISWA PGSD - Putri, Suci Utami (Universitas Pendidikan Indonesia, 2014)
The Curriculum 2013 for primary school education which is now applied in Indonesia put emphasis on thematic learning model using the scientific approach. The application of this curriculum has raised certain concerns on teachers and student teachers of primary school. The lack of confidence and the lack of mastery of science concepts by student teachers, especially those whose major are nonscience department have the potential to affect the quality of thematic science teaching when they carry out their duties in the future. Development of in-depth understanding from science material training program and its relevance to the curriculum 2013 using blended learning model can be one of the ways to overcome these problems. Blended learning is a learning strategy that combines offline or online interaction with face-to-face learning interaction. The training programs for in-depth understanding of science material using blended learning models is expected to increase the self-confidence, mastery of science concepts, and the ability to design a thematic science learning for elementary school student teachers. Keywords: science material training program, blended learning, preservice teacher program.